2016
DOI: 10.1021/acsami.6b04768
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-Size and Single-Crystal MoSe2 Atomically Thin Films Grown on GaN Substrate for Light Emission and Harvesting

Abstract: Two-dimensional (2D) atomic-layered semiconductors are important for nextgeneration electronics and optoelectronics. Here, we designed the growth of an MoSe 2 atomic layer on a lattice-matched GaN semiconductor substrate. The results demonstrated that the MoSe 2 films were less than three atomic layers thick and were single crystalline of MoSe 2 over the entire GaN substrate. The ultrathin MoSe 2 /GaN heterojunction diode demonstrated ∼850 nm light emission and could also be used in photovoltaic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 37 publications
(48 reference statements)
2
59
0
Order By: Relevance
“…Further investigation of PV performance of the junction was analyzed from current‐voltage ( I ‐ V ) curves as illustrated in Figure B. Device exhibits a high V oc of 0.62 V, while the PCE of the cell was 1.29%, which is less than the previously reported efficiencies for MoS 2 /Si and MoS 2 /GaAs SCs . Lin et al reported MoS 2 /hBN/GaAs heterostructure SC by introducing hexagonal boron nitride (hBN) in MoS 2 /GaAs heterojunction .…”
Section: Tmdcs‐based Heterojunction Pv Devicesmentioning
confidence: 91%
See 4 more Smart Citations
“…Further investigation of PV performance of the junction was analyzed from current‐voltage ( I ‐ V ) curves as illustrated in Figure B. Device exhibits a high V oc of 0.62 V, while the PCE of the cell was 1.29%, which is less than the previously reported efficiencies for MoS 2 /Si and MoS 2 /GaAs SCs . Lin et al reported MoS 2 /hBN/GaAs heterostructure SC by introducing hexagonal boron nitride (hBN) in MoS 2 /GaAs heterojunction .…”
Section: Tmdcs‐based Heterojunction Pv Devicesmentioning
confidence: 91%
“…Chen et al synthesized MoSe 2 layer on single‐crystal GaN via CVD furnace . MoSe 2 fabricated on GaN is composed of better electronic and optoelectronic properties.…”
Section: Tmdcs‐based Heterojunction Pv Devicesmentioning
confidence: 97%
See 3 more Smart Citations